Hubungan Harmonis antara Muslim dan Yahudi sejak Masa Kenabian sampai Masa Umayyah di Al-Andalus - Gumilar Irfanullah (Hayula: Jurnal Indonesia Studi Islam Multi-disiplin, 2017)
In some phases of history of relations between religious communities, there was a harmonious relationship and co-existence between Muslims and Jewish and also Christians. History recorded a relatifely harmonious relationship and merely productife especially in most Western part of Muslim world, al-Andalus. This paper attends to display the history of religious life that led to the peace, and thus it is importance to show cultivate messages of peace and tolerance in religious communitees. This paper presents data form History that was processed through historical analysys and generates an interesting conclusion, that religious diversity and beliefs, does not hinder people of different religions to practice each other live in harmony side by side, even work together to create a cultural creatifity in the field of art, science and literature. The result of study can serve as a comparison and a healing for conflict resolution which involves religion in it, like what happens between Israelits Jeiwsh and Palestinians Muslim.